Economic Impact Analysis of Climate Change on Sugarcane Production: An ARDL Model Approach - Dandi Fernanda; Eva Zunia Khoiryah; Ririn Wulandari; Mohammad Wasil (PT FORMOSA CENDEKIA GLOBAL, 2026)
Global climate volatility has created structural uncertainties threatening the supply stability of strategic commodities. This study aims to estimate the dynamic supply response of sugarcane in East Java to agro-climatic shocks and conventional production inputs over the 1995–2023 period. Using the Autoregressive Distributed Lag (ARDL) approach, this study models the market adjustment mechanism toward long-run equilibrium. Estimation results reveal that the sugarcane sector faces serious supply rigidity due to hydrological factors. Rainfall anomalies are identified as persistent negative supply shocks, triggering technical inefficiency due to waterlogging risks. On the other hand, the land area variable shows positive but inelastic elasticity, confirming the law of diminishing marginal returns on an aggregate scale. The finding that temperature and population variables are insignificant revises old theoretical assumptions, confirming that the sugarcane production function in tropical regions is more sensitive to hydrological constraints than thermal ones. The economic implication is that self-sufficiency strategies can no longer rely on high opportunity cost land extensification, but require investment reallocation towards climate risk mitigation technologies to improve supply curve efficiency.